2017
DOI: 10.1021/acs.chemmater.7b00890
|View full text |Cite
|
Sign up to set email alerts
|

Reaction and Space Charge Layer Formation at the LiCoO2–LiPON Interface: Insights on Defect Formation and Ion Energy Level Alignment by a Combined Surface Science–Simulation Approach

Abstract: In this contribution, we investigate the formation and evolution of LiCoO2–LiPON interfaces upon annealing using photoelectron spectroscopy. We identify interlayer compounds related to the deposition process and study the chemical reactions leading to interlayer formation. Based on the structure of the pristine interface as well as on its evolution upon annealing, we relate reaction layer and space charge layer formation to chemical potential differences between the two materials. The results are discussed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 60 publications
3
98
0
Order By: Relevance
“…Li concentration in Li x CoO 2 ). This new physics insight unifies the seemingly contradictory experimental observations [2][3][4]. Improved theoretical understanding also provides valuable design rules for the next generation of devices.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Li concentration in Li x CoO 2 ). This new physics insight unifies the seemingly contradictory experimental observations [2][3][4]. Improved theoretical understanding also provides valuable design rules for the next generation of devices.…”
mentioning
confidence: 60%
“…Solid-state electronic heterojunctions at solid-electrolyte/electrode interfaces play a critical role in determining ionic transport, and therefore performance, in these devices. Among various interfacial phenomena such as phase change [9], ionic distribution [2,10], and electrostatic potential drop [11][12][13], the formation of a "space-charge layer" at the electrode/solid-electrolyte interface is often cited as a barrier for lithium ion transport [14,15]. The driving force behind space-chargelayer formation is the chemical potential difference between contacting materials, which can result in depletion or enrichment of charged defects near the interface [16].…”
mentioning
confidence: 99%
“…In the O 1s region, the peak fitting also reveals that there is still adsorbed EC in the adlayer, as indicated by the low‐intensity O carbonyl (yellow) and O ring (cyan) peaks. A dominant peak appears at 531.3 eV (red), which was already present for the pristine LiCoO 2 thin film (black solid line), however, with much lower intensity, and which could be related to the formation of additional Li 2 O 2 or O ad species (cf. also with Figure ).…”
Section: Resultsmentioning
confidence: 91%
“…One possible way to determine the initial stages of the SEI formation at the EEI at the atomic/molecular level involves the use of surface science techniques, studying the interaction of individual components of electrolytes, such as the typical key component EC (or other electrolyte components like ionic liquids), with well‐defined model electrodes under idealized ultrahigh‐vacuum (UHV) conditions, which is focus of the ongoing work in our laboratory. Following a previous study on the interaction of EC with Li‐free and lithiated highly oriented pyrolytic graphite (HOPG) as model for the anode, we here report the results of a similar type of study on the interaction of EC with well‐defined LiCoO 2 electrode surfaces, both fully oxidized LiCoO 2 and partly reduced LiCoO 2− δ surfaces, as models for the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…Some sulfide SSEs such as Li 7 P 3 S 11 have only a 1D Li + ion diffusion path. [259][260][261] Unlike the sulfide and oxide SSEs, Li + ions would migrate from the electrode (LiCoO 2 ) toward the electrolyte (LiPON) rather than from electrolyte toward electrode upon their first contact, because the energy levels in LiPON were generally lower than the vacancy level in LiCoO 2 . [254] A potential slope at the initial period of the charging process, as presented in Figure 14b, suggested that the spacecharge layer was produced before the lithium deintercalation reaction of cathodes (such as a 4 V plateau for LiCoO 2 ).…”
Section: Origin Of the Interfacial Resistancementioning
confidence: 99%